UK anti-slavery policy at the border: Humanitarian opportunism and the challenge of victim consent to assistance. (September 2020) - Hadjimatheou, Katerina; Lynch, Jennifer
The UK's Modern Slavery Strategy, launched in 2014, gives Border Force Officers a key role as anti-slavery first responders, identifying and supporting victims at the border. Yet, while an estimated 94 percent of victims identified in the UK cross UK borders, in 2016 less than 3 percent of victim referrals were made at the border. This article draws on a series of in-depth interviews with a specialized Safeguarding and Anti-Trafficking (SAT) team within the UK Border Force to shed light on this discrepancy. In doing so, it takes forward critical debates about the coherence of humanitarian anti-slavery policy and the consistency of its ambitions with a continued prioritization by governments of security policy and immigration control. The article furthers two key arguments: first, that current policy around anti-slavery first response at the border is grounded in a rationale of 'humanitarian opportunism', which states that borders are sites of unique opportunity to identify and assist victims of trafficking, and that Border Force Officers therefore have a humanitarian duty to identify and assist victims; second, that the humanitarian opportunity is in reality far more restricted in practice than the policy rhetoric suggests, a fact that goes some way to explaining the very small numbers of those identified as trafficked and assisted at UK borders. Two key challenges to successful identification and support are identified: the first is EU freedom of movement, which in effect exempts European citizens from vulnerability screening by Border Force Officers; the second is the requirement that Border Force Officers obtain written consent from those identified as trafficked to being labelled a victim of crime before they can be offered support. The article puts forward some suggestions for how these challenges could be addressed for the benefit of those trafficked.